Influence of gusset plate connections and braces on the seismic performance of X-braced frames. - Roeder, Charles W. (Earthquake engineering & structural dynamics.)
Braced frames are one of the most economical and efficient seismic resisting systems yet few full-scale tests exist. A recent research project, funded by the National Science Foundation (NSF), seeks to fill this gap by developing high-resolution data of improved seismic resisting braced frame systems. As part of this study, three full-scale, two-story concentrically braced frames in the multi-story X-braced configuration were tested. The experiments examined all levels of system performance, up to and including fracture of multiple braces in the frame. Although the past research suggests very limited ductility of SCBFs with HSS rectangular tubes for braces recent one-story tests with improved gusset plate designs suggest otherwise. The frame designs used AISC SCBF standards and two of these frames designs also employed new concepts developed for gusset plate connection design. Two specimens employed HSS rectangular tubes for bracing, and the third specimen had wide flange braces. Two specimens had rectangular gusset plates and the third had tapered gusset plates. The HSS tubes achieved multiple cycles at maximum story drift ratios greater than 2% before brace fracture with the improved connection design methods. Frames with wide flange braces achieved multiple cycles at maximum story drift greater than 2.5% before brace fracture. Inelastic deformation was distributed between the two stories with the multi-story X-brace configuration and top story loading.